Efektivitas Konseling Kelompok dengan Teknik Strength Bombardment dalam Meningkatkan Resiliensi Diri Pada Mahasiswa yang Mengalami Fatherless - Adeliya Ramadhani; Alfin Siregar; Ade Chita Putri Harahap (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2025)
This study aims to examine the effectiveness of group counseling using the strength bombardment technique in enhancing self-resilience among students who experience fatherlessness. The research employed  quantitative approach with a quasi experimental design, specifically a non equivalent control group design, involving two groups an experimental group that received group counseling with the strength bombardment technique, and a control group that did not receive any treatment. The population consisted of all students from the Islamic Guidance and Counseling Education Study Program, class of 2024, totaling 186 students. The sample comprised 12 students from the same program who met the criteria for fatherlessness, and were purposively assigned to the two groups. The research instrument used was a self-resilience scale developed by Daulay  Indriani 2024, with measurements taken during the pretest and posttest stages. Data analysis was conducted using the Wilcoxon test in SPSS version 22, with a significance level of 0.05. The results indicated that before the intervention, all subjects in both groups had low levels of self-resilience 100%. After the intervention, the experimental group showed a significant increase, with 66.6% of students categorized as having high resilience, 16.7% in the very high category, and 16.7% in the moderate category, while the control group remained in the low category without any change. Based on the results, the Sig. 2-tailed value was 0.027. This study reveals that group counseling using the strength bombardment technique is effective in enhancing self resilience among students who experience fatherlessness.